The importance of anaemia in cerebral and uncomplicated falciparum malaria: role of complications, dyserythropoiesis and iron sequestration. - Phillips, R; Looareesuwan, S; Warrell, D; Lee, S; Karbwang, J; Warrell, M; White, N; Swasdichai, C; Weatherall, D (1986)
Ninety-four per cent of 169 patients with cerebral malaria developed anaemia (haematocrit less than 35 per cent) and 30 per cent required blood transfusion to maintain the haematocrit at more than 21 per cent. Anaemia was at its worst on admission in 58 patients (34 per cent); in the rest the haematocrit fell further, reaching its nadir one to 17 days later (mean 2.3 days). The mean lowest haematocrit was 24.3 +/- 7.2 per cent (+/- 1 SD) and the mean maximum fall was 7.9 +/- 5.6 per cent. Anaemia was more severe in patients with bacterial infection, retinal haemorrhages, schizontaemia and in pregnancy. The lowest haematocrit correlated with admission parasitaemia (r = -0.33, p less than 0.001), total serum bilirubin (r = -0.25, p less than 0.01) and serum creatinine (r = -0.22, p less than 0.01). In 23 patients with uncomplicated falciparum malaria the mean serum iron on admission was 53 micrograms/dl (range 16-157) and the mean serum ferritin 1773 ng/ml (range 170-10 000). There was a significant (p less than 0.001) rise in serum iron 96 h after starting antimalarial treatment; the serum ferritin declined slowly over several weeks. Stainable iron was present in all marrows examined and in eight patients the characteristic pattern of the anaemia of chronic disorders was seen. Seventy-three per cent of patients had dyserythropoiesis which was moderate to gross in 36 per cent. Dyserythropoiesis and erythrophagocytosis were often present on admission but sometimes appeared after the parasitaemia had cleared and persisted for at least three weeks into convalescence. These disturbances in iron metabolism and haemopoiesis are not completely explicable by red blood cell parasitisation. They may contribute more to the anaemia than has previously been recognised.